The downstairs girl - Lee, Stacey (Stacey Heather) (G.P. Putnam's Sons, 2019)
"1890, Atlanta. By day, seventeen-year-old Jo Kuan works as a lady's maid for the cruel Caroline Payne, the daughter of one of the wealthiest men in Atlanta. But by night, Jo moonlights as the pseudonymous author of a newspaper advice column for 'the genteel Southern lady'"--